Treaty Shopping beim Investorenschutz - eine Replik - Sebastian Dullien (Wirtschaftsdienst, 2015)
Im Juliheft 2015 veröffentlichte der Wirtschaftsdienst einen Aufsatz von Henning Klodt und Stefanie Lang zum Treaty Shopping. Sebastian Dullien weist auf eine seiner Auffassung nach fehlerhafte Darstellung des bilateralen Investitionsschutzabkommens zwischen Deutschland und Pakistan aus dem Jahre 1959 hin und die Autoren erläutern ihren Standpunkt in einer Erwiderung. – – Reply: The article by Klodt and Lang uses the Germany-Pakistan bilateral investment treaty from 1959 as an example of a treaty with investor-state dispute settlement (ISDS) provisions. Dullien insists that this treaty only contains a state-state-dispute settlement provision. Response: Klodt and Lang repeat that the above-mentioned treaty is the first to treat investment matters, but they concede that it is more of a state-state-dispute settlement process. They cast doubts on the preferability of such settlements.
Keywords: F53; F55; K33; 330; Auslandsinvestition; Gläubigerschutz; Anreiz; Multinationales Unternehmen; Schuldrecht; Internationales Investitionsrecht; Welt